Measuring Physical Violence and Rape Against Somali Women Using the Neighborhood Method. (June 2016) - Parcesepe, Angela; Stark, Lindsay; Roberts, Leslie; Boothby, Neil
This study was conducted to estimate prevalence of gender-based violence (GBV) among female Somalis in Ethiopian refugee camps and host communities, compare prevalence in camps and communities, and compare prevalence in flight and in camp. Systematic random sampling was used to select households in Awbare camp ( n = 85), Awbare town ( n = 76), and Kebribeyah camp ( n = 83). GBV was common and overwhelmingly domestic. Prevalence was higher in Awbare town than Kebribeyah camp. Women were at increased risk of GBV in camp compared with in flight. The domestic nature of GBV in humanitarian settings requires attention. Assumptions about violence in humanitarian settings should be further tested.